The organization of microtubules and Tau in oligodendrocytes: Tau pathology in damaged oligodendrocytes - Torii, Tomohiro; Miyasaka, Tomohiro; Misonou, Hiroaki (Frontiers in Cell and Developmental Biology, 2022)
Tau is abundantly expressed in neurons, however previous reports and our recent study showed tau also exist in oligodendrocytes. Also the expression levels of tau are dramatical changed in hypomyelination model rat and in demyelination region of stroke model mice. The review demonstrate microtubule and its binding partner Tau might be necessary for oligodendrocyte function based on previous reports.